A evolução do perfil conceitual de átomo por meio de atividades experimentais espectroscópicas - Lopes, Rodrigo Oliveira (2017)
The comprehension of atomic models is a very importante fator to understand a variety of concepts associated to the field of natural sciences. Adding to this, the fact that chemistry teachers have many difficulties during their activities when they have to teach this subject in classroom is a common problem. It is also a fact that high school students often show limitations in understanding the scientific concepts required by this subject and, therefore, there is an urgente necessity in developing methodologies which could improve the traditional teacher work when in classroom. Bearing this in mind, this work aims to investigate how didactic activities based on series of experiments can augment the conceptual acquisition and the evolution of thought about atoms in high school students. The actual research problem to be analyzed here i show and under what ways, series of experimentations can potentialize the evolution of individuals regarding the concepts of atomic models. To carry that out, a study has been made with a group of students in a private school in the city of Santa Maria – RS, according to action research methods involving the conceptual theory profile proposed by Eduardo Mortimer. Three student grupos (A,B and C) and the project activities happened in four distinct moments: a pretest, a regular background lecture, the experiments and a posttest according to Brazilian educational standards. The experiments used optical spectroscopy to discuss atomic models. Pretests, individual lab notebooks, class quizzes and posttests allowed to evaluate the students and the method. The analysis allowed to conclude that the students showed considerable development in acquisition of concepts since they showed to reach more advanced levels of understanding of atomic models showing the potential of the proposed teaching method. It was also possible to assess that even reaching higher levels of understanding of atomic models, it is difficult for students to abandon noncientific zones like sensorialism and substantialism. This brings about the need of improvement of further classroom methods which allow the students to outcome nonscientific conceptions. This proposal, however, has great potential to be used as standard for the students to reach the fourth conceptual zone, which is the quantum states of simple atoms.